El desarrollo psicolingüístico de las asociaciones verbales y la constitución de los cluster - Gonzales Moreyra, Raúl (1984)
Three psycholinguístic processes were studied in a sample of 30 boys between 7 and 12 years of age: paradigmatic associations, meaning consistency and categorial clusters. The results partially lend support to the hypothesis presentad by the author. A discussion of some of the consequences of the data is done relating them to the importance some associative structures have in relation to spontaneous categorial inclusion.